EIGENVALUES AND EIGENFUNCTIONS OF CERTAIN INTEGRAL OPERATORS (International journal of artificial intelligence, 2026)
This paper investigates the problem of determining eigenvalues and eigenfunctions of certain classes of integral operators. Special attention is given to Fredholm and Volterra integral operators with continuous and separable kernels. Using analytical methods, the spectral properties of these operators are studied, and illustrative examples are provided. The obtained results play an important role in functional analysis, integral equation theory, and applications in mathematical physics.